2017
DOI: 10.1080/1351847x.2017.1340320
|View full text |Cite
|
Sign up to set email alerts
|

The lead-lag relation between the stock and the bond markets

Abstract: I examine the relative informational efficiency of bonds and the underlying stocks through the lead-lag relation between their daily returns. I find that stock returns lead the returns of high yield bonds but not those of investment grade bonds, which indicates that the stock market is relatively more informational efficient than the bond market. The findings imply trading opportunities for the bonds that are highly sensitive to the release of new information. I also find that stocks detect impending defaults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
3
10
2
Order By: Relevance
“…This result differs from that of Tolikas (2018) who argues the any leading relation from stock to bonds returns only exists for speculative bonds and not investment grade bonds. Our results may differ as we consider sovereign bonds, whereas Tolikas only examines corporate bonds.…”
Section: Mean and Variance Causality And Spillovers Across Assetscontrasting
confidence: 93%
“…This result differs from that of Tolikas (2018) who argues the any leading relation from stock to bonds returns only exists for speculative bonds and not investment grade bonds. Our results may differ as we consider sovereign bonds, whereas Tolikas only examines corporate bonds.…”
Section: Mean and Variance Causality And Spillovers Across Assetscontrasting
confidence: 93%
“…The study further concludes that the daily bond returns are led by the daily stock returns. This indicates that the bond holders might have ample time to position their investments better (Tolikas, 2017). Further, (Kolluri, Wahab, & Wahab, 2015) adds that the Indian stock market is strongly influenced by the U.S. equity market.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research studies into the efficiency of financial markets have found that calendar anomalies in asset prices-or variations in asset returns that follow certain time-dimensional patterns and that are contrary to the concept of market efficiency-occur with surprising regularity (Buguk and Brorsen 2003;Nath and Dalvi 2004;Tolikas 2018). Calendar anomalies may take various effects: day-of-the-week, weekend, week-of-the-month, month-of-the-year, turn-of-the-month, turn-of-the-year, and Halloween.…”
mentioning
confidence: 99%
“…Many studies have been conducted in developed and developing countries to test the efficiency of the stock market (Poshakwale 1996;Buguk and Brorsen 2003;Nath and Dalvi 2004) and of the bond market (Conroy and Rendleman 1987;Tolikas 2018). The stock market is found to be more informationally efficient than the bond market (Tolikas 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation